Redescription and new record of the spongobiotic shrimp Periclimenaeus rastrifer Bruce, 1980 (Crustacea: Decapoda: Palaemonidae) from Taiwan - Ďuriš, Zdeněk; Šobáňová, Anna; Lin, Chia-Wei (Zootaxa, 2021)
The palaemonid shrimp Periclimenaeus rastrifer is here reported from Taiwan based on three specimens. It bears a feeble but distinct anterodorsal lobe on the first pleonite (not reported before). The mouthparts, not previously described, are also remarkable by a multidentate apex of the mandibular incisor, asymmetric distal endite of the second maxilla, and expanded dorsal lobe on the second maxilliped merus. The species is thus redescribed here. One of the examined specimens possesses an unusual rostrum, and malformed telson and uropodal spinulation; the latter specimen is described and illustrated in detail, including the mouthparts. Previously, the only species in the genus published in faunistic repors from Taiwan were P. wolffi Bruce 1993 and P. gorgonidarum (Balss, 1913) recorded from the Taiwan Strait, and the Green Island, respectively; P. rastrifer is reported here as the first of the genus from Taiwan mainland